(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
The proposal of this work is the study of the Canary Islands nationalistic project in America during the period of 1895-1933. There are two key moments in the history of Canary Islands nationalism in America. The first of these took place in Caracas, coinciding with the Cuban War of Independence, while the second came about in Havana when Spain was under the dictatorship of Primo de Rivera. The two attempts at construction of a Canary Islands nationalistic project in America also coincided with two crucial moments in Spanish and world history. These were the redistribution of colonial power with its loss of Cuba, Puerto Rico and the Philippines, and in the Spanish assumption of a brief protagonist attitude in North Africa.